Angiographic variation of the internal carotid artery and its branches in horses - Khairuddin, Nurul Hayah; Sullivan, Martin; Pollock, Patrick J. (The American College of Veterinary Surgeons, 2015)
OBJECTIVES: To record the angiographic anatomy of the equine internal carotid artery (ICA) using angiography techniques.